2021
DOI: 10.1177/18369391211009698
|View full text |Cite
|
Sign up to set email alerts
|

Invisible transitions: Transitions to school following different paths

Abstract: Most children starting primary school in Australia do so after attending early childhood education and participating in a transition to school programme. While this has become the expected pathway, it is not the one followed by all children and their families. In this article, we describe visible transitions as those that are known, understood and planned – that is, they follow the expected path. In contrast, invisible transitions occur when children and families arrive unexpectedly at school. Drawing on two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
4
0
5
Order By: Relevance
“…The inclusion of the child's perspective is an important dimension for understanding the relationship between learning and environmental factors. Following a children's participatory rights-based framework (Dockett & Perry, 2021), students should have a view on matters that affect them Lipponen et al, 2018). Children's own perspectives are crucial to understanding their school experiences and the aspects that contribute to their positive cognitive and socioemotional functioning.…”
Section: Children's Own Perspectives On Listening At Schoolmentioning
confidence: 99%
“…The inclusion of the child's perspective is an important dimension for understanding the relationship between learning and environmental factors. Following a children's participatory rights-based framework (Dockett & Perry, 2021), students should have a view on matters that affect them Lipponen et al, 2018). Children's own perspectives are crucial to understanding their school experiences and the aspects that contribute to their positive cognitive and socioemotional functioning.…”
Section: Children's Own Perspectives On Listening At Schoolmentioning
confidence: 99%
“…•Generate themes •There are four themes generated from the research: (1) preparation ( 2) communication and collaborations (3) Availablity of support (4) Barries to transition process Themes (Bornfreund & Ewen, 2021). Dockett & Perry (2021) suggested that this visit should begin before the school period begins. This is because children with special needs need longer time in terms of orientation and adaptation to school environment and class routines.…”
Section: Initial Codesmentioning
confidence: 99%
“…Interessen for overgange mellem dagtilbud og skole er bestemt ikke ny, og både dansk og international forskning peger på, at overgangen kan have stor betydning for børnene på både kort og lang sigt (Andreasen & Laustsen 2019;EVA 2016EVA , 2021Dockett & Perry 2001, 2012Broström 2003;DEA 2021;Egmont Fonden 2019;OECD 2017). Et studie fra VIVE (2019), der fulgte 5.000 børn født i 1995 fra deres skolestart til og med 22-årsalderen, viser, at børn med trivselsudfordringer ved skolestart generelt klarer sig dårligere senere i deres uddannelsesforløb.…”
Section: Forskning I Overgange Og Brobygningunclassified
“…Den australske forsker Robert Perry, der i årtier har arbejdet med overgange fra dagtilbud til skolen, har flere bud på vigtige elementer i brobygningsprocesser (Dockett & Perry 2001, 2007. Et element er, at børnene skal opleve genkendelighed og kontinuitet og fortsaette med at laere på måder, som hidtil har vaeret vellykkede for dem.…”
Section: Forskning I Overgange Og Brobygningunclassified